The Influence of Individual Diversity on Team Performance at the Pagar Alam City Department of Agriculture - Sela Sela; Sastra Mico; Nurlela Nurlela (The Future of Education Journal, 2026)
This study aims to empirically identify and analyze the influence of individual diversity on team performance at the Pagar Alam City Agriculture Office. In line with the demands of bureaucratic reform, understanding the heterogeneity of civil servants within the organizational structure of the public sector is crucial for improving service effectiveness. The research approach used is quantitative, employing an associative method. The population in this study comprises all 91 employees at the relevant agency, with the sample determined using a saturated sampling method (census). Primary data collection was conducted by distributing a structured Likert-scale questionnaire that had passed validity and reliability tests. Data analysis techniques included descriptive analysis, simple linear regression, Pearson’s correlation analysis, analysis of the coefficient of determination (R²), and a partial t-test, all performed using SPSS software. The results of the simple linear regression analysis yielded the equation Y = 6.212 + 0.388X. The t-test results showed a calculated t-value of 7.543, which was significantly greater than the critical t-value of 1.662 at a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.390 indicates that individual diversity contributes 39% to the variation in team performance, while the remainder is controlled by external variables. The findings of this study demonstrate that individual diversity has a positive and significant impact on team performance at the Pagar Alam City Department of Agriculture. Inclusive diversity management achieved through the optimization of intergenerational communication, gender equality, and the synergy of academic competencies has been shown to accelerate productivity in public-sector organizations.